A three‐dimensional analysis of the endolymph drainage system in Ménière disease. (21st July 2016) - Monsanto, Rafael da Costa; Pauna, Henrique F.; Kwon, Geeyoun; Schachern, Patricia A.; Tsuprun, Vladimir; Paparella, Michael M.; Cureoglu, Sebahattin
Abstract : Objectives/Hypothesis: To measure the volume of the endolymph drainage system in temporal bone specimens with Ménière disease, as compared with specimens with endolymphatic hydrops without vestibular symptoms and with nondiseased specimens Study Design: Comparative human temporal bone analysis. Methods: We generated three‐dimensional models of the vestibular aqueduct, endolymphatic sinus and duct, and intratemporal portion of the endolymphatic sac and calculated the volume of those structures. We also measured the internal and external aperture of the vestibular aqueduct, as well as the opening (if present) of the utriculoendolymphatic (Bast's) valve and compared the measurements in our three study groups. Results: The volume of the vestibular aqueduct and of the endolymphatic sinus, duct, and intratemporal endolymphatic sac was significantly lower in the Ménière disease group than in the endolymphatic hydrops group ( P <.05). The external aperture of the vestibular aqueduct was also smaller in the Ménière disease group. Bast's valve was open only in some specimens in the Ménière disease group. Conclusions: In temporal bones with Ménière disease, the volume of the vestibular aqueduct, endolymphatic duct, and intratemporal endolymphatic sac was lower, and the external aperture of the vestibular aqueduct was smaller as compared with bones from donors who had endolymphatic hydrops without vestibular symptoms and with nondiseased bones. The open status of the Bast's valve in the Ménière disease group could be secondary to higher retrograde endolymph pressures caused by smaller drainage systems. These anatomic findings could correlate with the reason that some patients with hydrops develop clinical symptoms, whereas others do not. Level of Evidence: N/A Laryngoscope, 127:E170–E175, 2017